SOME FEATURES OF THE LAW RELATIONSHIP OF CIVIL LIABILITY OF PUBLIC ENTITIES AND INSTITUTIONS - Pavlovich, Anisimov; Pavlovich, Kamyshanskii; Evgenevich, Karnushin (Revista Inclusiones, 2020)
The article deals with the civil law liability of public entities and institutions as a special kind of civil law relationship. There are analyzed features of this law relationship in comparison with the general theoretical understanding of civil law relationship of liability, which is not complicated by the peculiarities of the law status of a public legal entity. Along with the established notions of law liability, it is proposed to consider liability as a special mental attitude of the offender to the actions he performs, or to his inactivity. Depending on this circumstance, the extent of the fault and the amount of liability to compensate the losses can be determined. In its nature liability is considered a special kind of law relationship. Civil law liability is a special protective law relationship, which allows not only to restore the violated civil rights, but also serves as a deterrent, ensuring the stability of civil turnover through the formation of internal mental attitudes to the lawful behavior of the obliged persons (parties).